Proceso atención de enfermería en paciente de 32 años con embarazo ectópico roto. - León Vera, Angee Maylin (2021)
The present clinical case was implemented in the Basic Hospital of Dr. Rafael Serrano López, it belongs to a 32-year-old female patient, entering the emergency area accompanied by her conscious husband, oriented in time, space and person with a clinical picture of 5 hours of evolution characterized by moderate pain in the region of the hypogastric and the right iliac fossa, tachycardia, malaise, amenorrhea, date of last menstruation (LMP) six weeks, with positive pregnancy test, in ultrasound an empty uterus, right ovary with presence of a 25 x 25 mm corpus luteum that resembles a cyst, the presence of fluid is evidenced in the pelvic area, laparoscopy is continued, an ectopic pregnancy is found in the fallopian.